The self-entrepreneurship in a context of precarious work an analysis of the factors that influence young people to work informally: uma análise dos fatores que influenciam os jovens a atuar na informalidade (Management and Connections Journal, 2024)
The high levels of unemployment and the disruption of the labor market were conducive to strengthening entrepreneurship and informality in the country, as a solution for the unemployed contingent. This way of entering the market mainly attracts young people who see this alternative as a way of obtaining income. In this sense, this article sought to verify the factors that influenced young people to be informally self-employed. The approach was qualitative, and whose research strategy used was the biographical method, through analysis of the life history of five young people from the city of Aracaju-SE. The results show that young informal self-entrepreneurship occurred mostly out of necessity, due to socioeconomic conditions, such as low education and unemployment, and also the desire for autonomy and independence at work.
Keywords: self-entrepreneurship; job market; informality; young people